A survey on the application of accounting information system in organization in Malaysia / Jamalludin Helmi Hashim …[et al.] - Hashim, Jamalludin Helmi; Nias Ahmad, Mohamad Azmi; Abdullah, Norlaila; Abdul Rahim, Kamaruzzanan (2004)
This survey was conducted to gain understanding on the application of Accounting Information System in organization in Malaysia. The results of this study show that, the most preferred accounting software is Microsoft Excel with the main reason are cost and its simplicity. PC base is the most preferred type of hardware and Microsoft Access is the most popular database used regardless of the organization size. It was found that cost and effectiveness, either individually or in combination of both, are fundamental for most of the respondents in the selection of hardware.